Three-year experience with immediate extubation in pediatric patients after congenital cardiac surgery - Tirotta, Christopher F. (J Cardiothorac Surg, 2020)
BACKGROUND: In pediatric cardiac anesthesiology, there is increased focus on minimizing morbidity, ensuring optimal functional status, and using health care resources sparingly. One aspect of care that has potential to affect all of the above is postoperative mechanical ventilation. Historically, postoperative ventilation was considered a must for maintaining patient stability. Ironically, it is recognized that mechanical ventilation may increase risk of adverse outcomes in the postoperative period. Hence, many institutions have advocated for immediate extubation or early extubation after many congenital heart surgeries which was first reported decades ago. METHODS: 637 consecutive patient charts were reviewed for pediatric patients undergoing cardiac surgery with cardiopulmonary bypass. Patients were placed into three groups. Those that were extubated in the operating room (OR) at the conclusion of surgery (Immediate Extubation or IE), those that were extubated within six hours of admission to the ICU (Early Extubation or EE) and those that were extubated sometime after six hours (Delayed Extubation or DE). Multiple variables were then recorded to see which factors correlated with successful Immediate or Early Extubation. RESULTS: Overall, 338 patients (53.1%) had IE), 273 (42.8%) had DE while only 26 patients (4.1%) had EE. The median age was 1174 days for the IE patients, 39 days for the DE patients, whereas 194 days for EE patients (p < 0.001). Weight and length were also significantly different in at least one extubation group from the other two (p < 0.001). The median ICU LOS was 3 and 4 days for IE and EE patients respectively, whereas it was 9.5 days for DE patients (p < 0.001). DE group had a significant longer median anesthesia time and cardiopulmonary bypass time than the other two extubation groups (p > 63,826.88 < 0.001). Regional low flow perfusion, deep hypothermia, deep hypothermic circulatory arrest, redo sternotomy, use of other sedatives, furosemide, epinephrine, vasopressin, open chest, cardiopulmonary support, pulmonary edema, syndrome, as well as difficult intubation were significantly associated with delayed extubation (IE, EE or DE). CONCLUSIONS: Immediate and early extubation was significantly associated with several factors, including patient age and size, duration of CPB, use of certain anesthetic drugs, and the amount of blood loss and blood replacement. IE can be successfully accomplished in a majority of pediatric patients undergoing surgery for congenital heart disease, including in a minority of infants.